2022
DOI: 10.1186/s13568-021-01342-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic Escherichia coli reporter strain for screening DNA damaging agents

Abstract: The presence of pollutants in soil and water has given rise to diverse analytical and biological approaches to detect and measure contaminants in the environment. Using bacterial cells as reporter strains represents an advantage for detecting pollutants present in soil or water samples. Here, an Escherichia coli reporter strain expressing a chromoprotein capable of interacting with soil or water samples and responding to DNA damaging compounds is validated. The reporter strain generates a qualitative signal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 63 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…The bacterial cell, and DNA damage induced by the nanoparticles were evaluated using biosensors containing the promoter regions of the genes uspA, recA and fabA , fused to the blue chromo‐protein AmilCP, which construction was described in Mora‐Garduño et al. (2022). To determine general stress, DNA damage and membrane damage respectively, a biosensor reporter strain was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial cell, and DNA damage induced by the nanoparticles were evaluated using biosensors containing the promoter regions of the genes uspA, recA and fabA , fused to the blue chromo‐protein AmilCP, which construction was described in Mora‐Garduño et al. (2022). To determine general stress, DNA damage and membrane damage respectively, a biosensor reporter strain was used.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of cell and DNA damage using biosensors The bacterial cell, and DNA damage induced by the nanoparticles were evaluated using biosensors containing the promoter regions of the genes uspA, recA and fabA, fused to the blue chromo-protein AmilCP, which construction was described in Mora-Garduño et al (2022).…”
Section: Generation Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…As a proof-of-concept, a previously reported plasmid bearing the recA promoter controlling the expression of a chromoprotein (AmilCP) [16] was transformed into BW25113 and ∆recA strains to evaluate the sensitivity of the reporter plasmid in the parental and mutant genetic backgrounds. Transformant cells were tested as described previously and transformants were selected in LB-ampicillin (200 µg/mL) [16]. Plates were recorded using a digital camera.…”
Section: Reporter Strainsmentioning
confidence: 99%
“…We showed that the silver NPs produced cell membrane and DNA damage, and that the plausible mechanism of both damaged structures is the production of ROS [15]. The value of bioreporter strains is that the effect of antimicrobials and nanomaterials may be determined based on primary damage information in vivo [16].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation